Association between white line disease and sole ulcers with certain milk components in Simmental cows - Ninković, M; Žutić, J; Arsić, S; Zdravković, N; Zurovac Sapundžić, Z; Glišić, D; Bojkovski, J; Giadinis, ND; Panousis, N (Journal of the Hellenic Veterinary Medical Society, 2023)
Lameness is one of the high influence production illnesses in intensive dairy production farming, it reduces milk yield and can also negatively affect the quality of milk. Many factors can affect the production of milk components. In addition race, nutrition, milk yield, various metabolic disorders, and lameness can have an effect on the synthesis of milk components. White line disease and sole ulcers are widespread hoof diseases of cows in tied-holding systems. Albeit the main cause of lameness, associations between claw disorders of cows and variation of milk components haven’t been widely studied in Simmental cows. The objective of our study was to investigate the effect of white line disease and sole ulcers on the production of milk components of Simmental dairy cows kept in the small households in Mačva locality, Serbia. Cows were selected with a history of lameness. A total of 3 groups of cows: affected by white line disease (n=12), sole ulcers (n=12), and healthy cows (n=12) in the early stage of lactation were selected for analysis of milk components. Milk components (milk protein, fat, and non-fat dry matter) were analyzed using Lactoscan S. Significance of differences in milk component characteristics between white line disease, sole ulcers, and healthy groups were tested using a Kruskal-Wallis multiple comparisons test. The contents of milk fat of cows affected by white line disease and cows affected by sole ulcers were significantly lower than those of non-lame cows: 3.80%, 3.69%, and 4.18%, respectively (both p<0.05). However, differences in the contents of milk protein and the contents of non-fat dry matter cows affected by white line disease, sole ulcers, and in health cows were not significantly different (p>0.05). Our results indicate that hoof diseases of cows namely whitee line disease and sole ulcers, significantly reduce the milk fat production in lame Simmental cows.